Rediscovering Consumer-Producer Involvement: A Network Perspective on Fair Trade Marketing in the UK - Nicholls, A; Alexander, A (2006)
Purpose-The paper aims to investigate the value of a network perspective in enhancing the understanding of the business to consumer marketing of high-involvement product categories. This is achieved through the analysis of the development of fair trade marketing in the UK. Design/methodology/approach-The paper addresses the research question through an analysis of relevant literatures from both marketing and other disciplinary areas. The paper is thus multidisciplinary in nature. Findings from a series of in depth, semi-structured interviews with senior representatives of a fair trade wholesaler, of a specialist fair trade brand, of supermarket retailers involved with fair trade and of other fair trade labelling and support organisations are reported and discussed. Findings-The relevance of an actor network theory (ANT) informed interpretation of the development of the fair trade marketing network is revealed. Its emphases on the processes of exchange and the role of human and non-human actants in enabling interactions within the network are shown to be important. fair trade marketing is shown as occurring within an unfolding network of information exchanges. Analysis of this emerging network highlights a shift of emphasis in fair trade marketing from the fair trade process to fair trade products and, latterly, fair trade places. Originality/value-The paper highlights the requirement for further conceptualisation of the business to consumer marketing of high-involvement product categories, and reveals the potential of ANT as one approach to meet this need. The paper also provides a detailed insight into the development of fair trade marketing in the UK.